Within-day energy deficiency and reproductive function in female endurance athletes - Fahrenholtz, I. L.; Sjödin, A.; Benardot, D.; Tornberg, Å . B.; Skouby, S.; Faber, J.; Sundgot-Borgen, J.; Melin, A. (Scandinavian Journal of Medicine & Science in Sports, 2018)
We aimed to estimate and compare within-day energy balance (WDEB) in athletes with eumenorrhea and menstrual dysfunction (MD) with similar 24-hour energy availability/energy balance (EA/EB). Furthermore, to investigate whether within-day energy deficiency is associated with resting metabolic rate (RMR), body-composition, S-cortisol, estradiol, T3, and fasting blood glucose. We reanalyzed 7-day dietary intake and energy expenditure data in 25 elite endurance athletes with eumenorrhea (n=10) and MD (n=15) from a group of 45 subjects where those with disordered eating behaviors (n=11), MD not related to low EA (n=5), and low dietary record validity (n=4) had been excluded. Besides gynecological examination and disordered eating-evaluation, the protocol included RMR-measurement; assessment of body-composition by dual-energy X-ray absorptiometry, blood plasma analysis, and calculation of WDEB in 1-hour intervals. Subjects with MD spent more hours in a catabolic state compared to eumenorrheic athletes; WDEB <0 kcal: 23.0 hour (20.8-23.4) vs 21.1 hour (4.7-22.3), P=0.048; WDEB <-300 kcal: 21.8 hour (17.8-22.4) vs 17.6 hour (3.9-20.9), P=0.043, although similar 24-hour EA: 35.6 (11.6) vs 41.3 (12.7) kcal/kg FFM/day, (P=0.269), and EB: -659 (551) vs -313 (596) kcal/day, (P=0.160). Hours with WDEB <0 kcal and <-300 kcal were inversely associated with RMRratio (r=-0.487, P=0.013, r=-0.472, P=0.018), and estradiol (r=-0.433, P=0.034, r=-0.516, P=0.009), and positively associated with cortisol (r=0.442, P=0.027, r=0.463, P=0.019). In conclusion, although similar 24-hour EA/EB, the reanalysis revealed that MD athletes spent more time in a catabolic state compared to eumenorrheic athletes. Within-day energy deficiency was associated with clinical markers of metabolic disturbances.